What do project managers need to know to succeed in face-to-face communication?. Issue 1 (1st January 2021) - Shakeri, Hedieh; Khalilzadeh, Mohammad; Raslanas, Saulius; Zavadskas, Edmundas Kazimieras
Abstract: Despite emphasising the great importance of project communications to enhance success in the literature, there are few studies underlining the application of psychology to project communications, and no studies regarding the identification and analysis of factors affecting face-to-face communications with stakeholders in different situations. The research here aims to fundamentally address this shortcoming. The factors affecting face-to-face communications and different communication situations have been identified by interview with several experts in psychology and project managers working in oil and gas megaprojects. The data have been analysed by using two questionnaires and the hybrid Fuzzy DEMATEL-ISM and BWM methods. The final results show that the importance of each of these effective factors in face-to-face communication varies in different situations, and that some of these factors influence each other and some are influenced by one or another. Proxima has the greatest influence on other factors. Also, body language has great influence on other factors. The results of the current study could still serve as a reflection of what might be expected at a more general level for face-to-face communications to support good communications planning. The Video Neuro advertising Recommender System improved by applying the obtained research results.